2009
DOI: 10.1128/iai.01173-08
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatisPolymorphic Membrane Protein D Is an Oligomeric Autotransporter with a Higher-Order Structure

Abstract: Chlamydia trachomatis is a globally important obligate intracellular bacterial pathogen that is a leading cause of sexually transmitted disease and blinding trachoma. Effective control of these diseases will likely require a preventative vaccine. C. trachomatis polymorphic membrane protein D (PmpD) is an attractive vaccine candidate as it is conserved among C. trachomatis strains and is a target of broadly cross-reactive neutralizing antibodies. We show here that immunoaffinity-purified native PmpD exists as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
92
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(110 citation statements)
references
References 55 publications
9
92
0
2
Order By: Relevance
“…4C). The in vitro formation of Pmp21-D oligomers is in agreement with earlier findings which indicated that the C. trachomatis homologue of Pmp21, PmpD, is part of a protein complex on the EB cell surface (24). Moreover, it was reported that Pmps of Chlamydia psittaci also occur in supramolecular complexes (50).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…4C). The in vitro formation of Pmp21-D oligomers is in agreement with earlier findings which indicated that the C. trachomatis homologue of Pmp21, PmpD, is part of a protein complex on the EB cell surface (24). Moreover, it was reported that Pmps of Chlamydia psittaci also occur in supramolecular complexes (50).…”
Section: Discussionsupporting
confidence: 79%
“…Nevertheless, these fungal adhesins form cell surface amyloid patches of arrayed adhesin molecules ("adhesin nanodomains") 100-1000 nm in size, thus binding ligands with high avidity (67,68). It is tempting to speculate that the flower-like structures observed by EM in affinity-enriched preparations of endogenous PmpD-containing protein complexes might possibly represent the in vivo version of the Pmp21 protofibrils detected in vitro in this study (24). The data presented here are compatible with the idea that oligomeric Pmp complexes might enhance the chlamydial cell's capacity for adhesion to human epithelial cells and be important for the initial step in infection.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…C. trachomatis serovar L2-infected L929 suspension cultures were harvested by centrifugation at 0, 12, 24, 30, and 36 h postinfection and lysed by Dounce homogenization, and cellular fractionation was performed as previously described (9,18,53). Insoluble and soluble fractions were analyzed by Western blotting using anti-CT153, anti-MOMP, or anti-chlamydial protease-like activity factor (CPAF) (16) Abs.…”
Section: Methodsmentioning
confidence: 99%
“…To overcome the host immunity barriers, and establish the successful infection, chlamydia may utilize virulence factors as previously proposed [10]. Many virulence factor candidates have been identified, such as the polymorphic outer membrane autotransporter family of proteins [11,12], the putative large cytotoxin [13], stress response proteins [14], and chlamydial secretion effectors [15][16][17]. It is known that C. trachomatis organisms can secrete numerous proteins into host cell cytoplasm [18,19].…”
Section: Introductionmentioning
confidence: 99%